A biomimetic fluorescent chemosensor for highly sensitive zinc(ii) detection and its application for cell imaging. Issue 58 (26th September 2018) - Yan, Rui; Wang, Zhi; Du, Zongliang; Wang, Haibo; Cheng, Xu; Xiong, Junjie
Abstract : To fabricate a novel biomimetic fluorescent chemosensor, PSaAEMA- co -PMPC was synthesized via atom transfer radical polymerization, and this copolymer could be used for the detection of zinc(ii ) and cell imaging. Abstract : To fabricate a novel biomimetic fluorescent chemosensor, PSaAEMA- co -PMPC was synthesized via atom transfer radical polymerization, and this copolymer could be used for the detection of zinc(ii ) and cell imaging. A series tests with various metal ions verified the specific fluorescence response behavior. This novel biomimetic fluorescent chemosensor exhibits excellent selectivity for Zn 2+ ions over a wide range of tested metal ions in an aqueous solution. Moreover, cytotoxicity and bio-imaging tests were conducted to study the potential bio-application of the chemosensor. Owing to the biomimetic portion (phosphorylcholine), this copolymer possesses outstanding biocompatibility and could clearly image cells. The results indicated that PSaAEMA- co -PMPC has great potential for application in zinc(ii ) detection and cell imaging.